Exploring and Assessing Government Website as an Instrument of E-Governance at the Local Government Level in Pangasinan - Legaspi, Perla E; Marigza, Rolando B (ASEAN Multidisciplinary Research Journal, 2021)
This research primarily aims to gain an understanding of the current status of local governments in terms of e-governance through the use of government websites. This study is a mixed-method research, a combination of the quantitative and qualitative research approach. For the qualitative part, the researchers conducted face-to-face interviews, telephone interviews, and systematic observations in exploring the trends, thoughts, and opinions of the participants to delve into a deeper understanding of the contents and features of city government websites. For the quantitative approach, a survey was conducted over 2,410 households using a questionnaire to determine the awareness, extent of availability, and satisfaction of the respondents on the resources and services accessible online. The extent of availability was determined by the respondents who are aware of the government website. And based on the respondents who availed of the resources, the extent of satisfaction was measured. The researchers considered the barangays under the Central Business District (CBD) of the cities of Dagupan, Alaminos, Urdaneta, and San Carlos to be the sources of data. Analysis of the responses demonstrated that almost half of the respondents of the four cities are aware of the web presence of the government websites of the four cities. In terms of satisfaction with the availed services, the majority of the respondents are slightly satisfied. The results also indicated that online resources and services online are not fully utilized. Hence, these are not enough to satisfy the needs of the respondents. On this basis, it is recommended that the national government should come up with a policy on the strict implementation of e-Governance through the use of government websites at the local government level. With this national policy in place, the local governments can also come up with local policies on the strict implementation of online services such as online registration, payment through banks or Bayad Centers, online processing of business permits, and other services.